ABOUT THE METHODOLOGY OF FORMATION IN PRESCHOOLERS OF THE SIZES AND SIZES OF OBJECTS - Mardanov Eshim Muratovich; Ostanov Kurbon; Achilov Utkir Isomitdinovich; Totliev Ulmas Khusniddin oglu; Abdullaeva Dildora Mamarakhimovna (Scholar Express Journal, 2021)
This article examines some of the issues of the methodology for the formation of the sizes and sizes of objects in preschoolers. Emphasizing that the sizes of objects children learn mainly by sensory methods in the process of examination, comparison and comparison, grouping, and values - by measuring objects and using numbers for the purpose of quantitative assessment, the sequence of mastering values in preschool age is given, ways of mastering by children of preschool age measurement of quantities, as well as methodological requirements for teaching children of five years of measuring activity.
Keywords: Size; value; measurement; development